2021
DOI: 10.1177/17543371211063124
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory assessment of a head impact sensor for youth soccer ball heading impacts using an anthropomorphic test device

Abstract: Recent advances in technology have enabled the development of instrumented equipment, which estimate the head impact kinematics of athletes in vivo. One such headband-mounted impact sensor is the SIM-G (Triax Technologies, Norwalk, CT, USA), which has been previously used to investigate the biomechanics of soccer heading by human subjects. Previous studies have evaluated the accuracy of the SIM-G for pure rotation and pendulum, impulse hammer and drop rig impacts. The current study used a soccer ball heading m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…From the same on-field soccer head impact dataset [ 54 ], we evaluated the rate and interval between multiple headers on the field and found that at the 95th percentile, there were 6 and 4 impacts per hour for boys and girls, respectively, with an interval of 8 min. The most typical pattern for repeated impact was a single ‘high’, and 4 to 5 ‘median’ level loads.…”
Section: Methodsmentioning
confidence: 99%
“…From the same on-field soccer head impact dataset [ 54 ], we evaluated the rate and interval between multiple headers on the field and found that at the 95th percentile, there were 6 and 4 impacts per hour for boys and girls, respectively, with an interval of 8 min. The most typical pattern for repeated impact was a single ‘high’, and 4 to 5 ‘median’ level loads.…”
Section: Methodsmentioning
confidence: 99%